Importance of Morphometric Measurement to Predict Productivity Traits for Palestine Assaf Sheep - Ikram BenSouf; Medhat Wild ALI; Angham Bani Odeh; Muayad Salman; Naceur M’Hamdi (Agricultural Sciences: Techniques and Innovations Vol. 2, 2025)
Assaf sheep, created through crossbreeding Awassi and East Friesian breeds, are pivotal to Palestine’s dairy production due to their adaptability to semi-arid climates and high milk yields. The hardy Awassi lends versatility, while the East Friesian excels in dairy productivity. Studies of morphometric and udder traits like body length, chest girth, udder depth, and teat positioning reveal strong links to lactation efficiency and growth rates, driving advancements in breeding strategies. Genomic tools, including single-nucleotide polymorphism (SNP) analysis and genome-wide association studies (GWAS), refine selection criteria for economic traits. Community-based breeding programs (CBBPs) foster sustainability, genetic progress, and resource optimisation through grassroots collaboration. Integrated phenotypic assessments and advanced computational methods, such as genomic selection algorithms and Bayesian models, enhance heritability predictions and identify superior candidates. Combining traditional practices with innovative genetic profiling, Assaf sheep development exemplifies the synergy between tradition and innovation, ensuring the sustainability and economic viability of Palestine’s dairy systems while preserving critical genetic diversity for future adaptability.